Penurunan Reject Rate Penyok Body Pada Proses Assembly Dengan Metode DMAIC Di PT.XYZ - Setiawan, Hendry; Raharjo, Jani (Jurnal Titra, 2019)
The research was conducted to identify the root cause of rejects on spin on products in the assembly process of PT. XYZ. It aims to determine the right improvement to reduce the reject rate on spin on products. This study applies the pareto chart and cause effect diagram to describe and determine the root cause of the problem. The proposed improvement is to apply a damper to the shutter. The results of implementation improvement bear positive result and reduce the project rate. Results before improvement are worth 0.19%, and after improvement worth 0.13%.